2007 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--2805
|View full text |Cite
|
Sign up to set email alerts
|

Academic Integrity Among Engineering Undergraduates: Seven Years Of Research By The E^3 Team

Abstract: Engineering from U-M. Dr. Finelli is responsible for advising the U-M College of Engineering on educational endeavors, conducting research in engineering education, planning and facilitating workshops for faculty and graduate student instructors, and generating a community of researchers in engineering education. She is also a member of the U-M Steering Committee for the President's Ethics in Public Life Initiative and the College of Engineering's Diversity and Outreach Council. Dr. Finelli is a member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Criterion 10 requires students to receive "knowledge of contemporary issues." E3 Team (Exploring Ethical decision-making in Engineering) studies the lack of ethics in engineering graduates [3]. A study quoted by the E3 Team shows that 60% of the 34,000 students surveyed admitted that they copied in the faculty once and 35% several times (copy on homework, projects or exams).…”
Section: The Academic Ethicsmentioning
confidence: 99%
“…Criterion 10 requires students to receive "knowledge of contemporary issues." E3 Team (Exploring Ethical decision-making in Engineering) studies the lack of ethics in engineering graduates [3]. A study quoted by the E3 Team shows that 60% of the 34,000 students surveyed admitted that they copied in the faculty once and 35% several times (copy on homework, projects or exams).…”
Section: The Academic Ethicsmentioning
confidence: 99%
“…Students' characterization of (peer) oral exams as assessments focused on evaluating deeper levels of understanding (Table VI) hints at another aspect of oral exams potentially impacting academic integrity -their meaningfulness. It has been argued that meaningful assessment engenders greater motivation among students to learn and showcase their knowledge, creativity, and originality before the instructor and peers, which in turn curbs cheating [112]- [114]. This motivation is closely related to the intimate desire of students to develop their academic and professional identities, which necessarily entails valuing authentic authorship and original thought, taking pride in one's own work, and empowering one's own character through a commitment to intellectual honesty and professionalism [103], [104], [115].…”
Section: Academic Integritymentioning
confidence: 99%
“…Yet the inclusion of ethics instruction is critical. Studies have reported engineers to have higher incidences of ethical transgressions than other majors [1,2], with cheating in university situations a strong predictor of unethical behavior in the workforce [2]. In fields such as civil engineering, and others where public safety is at risk, this is troubling.…”
Section: Introductionmentioning
confidence: 99%